PERTANGGUNGJAWABAN iNOTARIS iYANG iMELANGGAR iPRINSIP iKETIDAKBERPIHAKAN iDALAM iMEMBUAT iAKTA i (STUDI iPUTUSAN: i2750K/PDT/2018) - Andre Darmawan; Benny Djaja (Fakultas Hukum Universitas Tarumanagara, 2021)
Notary ipublic iis ithe icompetent ipublic iofficial ito idraw iup ian iauthentic ideed ias ilong ias ithe idrawing iup iof ia icertain ideed iis inot ispecifically imade ito ithe iother ipublic iofficials. iAccording ito iArticle i16 iparagraph i(1) ipoint ia iLaw iof iThe iRepublic iof iIndonesia iNumber i2 iOf i2014 iOn iOffice iOf iNotary iPublic, iin iperforming ihis/her ioffice, ia iNotary iPublic ishall ibe iobligated ito iact ihonestly, iaccurately, iindependently, inon-unilaterally, iand imaintain ithe iinterests iof ithe irelevant iparties iin iany ilegal iaction. iThe ideed ithat iis imade iby iNotary iPublic imust ibe imade based ion iboth iparties’ iagreements. However, iin ithe iSupreme iCourt Verdict Number i2750 iK/PDT/2018, Notary iPublic iEM iignored ithe ilaw, she ididn’t igive iany ilegal iadvice irelated ito ithe ideeds iand isided iwith some iof ithe iparties ito iperform iunlawful iprocedures. iThe iauthor examines ithe iproblem iusing inormative ilegal iresearch imethods iwhich are isupported iby isome iinterviews iwith ithe iones iwho iare iexperts iin the ifield iof iNotary iPublic Law. iViolation iby ia iNotary iPublic iof ithe provisions ias ireferred ito in ithe iArticle i16 iparagraph i(1), imaking ia deed ionly ihave ia ipower iof ievidencing ias ia ideed iprivately imade ior making ithe isame inull iand ivoid ican ibe ia ireason ifor ia iparty isufferingia iloss ito iclaim ifor iexpenses, icompensation, iand iinterest ito ithe iNotary Public.